Impelemetation of Devotional Rights on Accessibility and Communication Based on Undang-Undang Nomor 8 Tahun 2016 Concerning Disabilities - Hendro Valence Luhulima (The Center for Disability Studies and Services Brawijaya University, 2018)
This research discusses the implementation of the right of the Deaf to accessibility and communication by the Government of Indonesia based on Law No. 8 of 2016 concerning Persons with Disabilities. Normative-empirical legal research used in this research. Due to time constraints, sampling was limited to Yogyakarta Special Region based on purposive sampling. This research does not focus on efforts to generalize, but rather emphasizes the meaning of a phenomenon under study. The results of this research is that the rights of Deaf people to accessibility and communication have not been fully implemented according to the mandate of Law No. 8 of 2016 concerning Persons with Disabilities. However, this does not mean that the rights of the Deaf are not fulfilled at all, but in the stage of development. This is because there are two conditions that researcher find among Deaf people, namely Deaf people whose rights have been fulfilled, and Deaf people whose rights have not been fulfilled.